2015
DOI: 10.1038/ejhg.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Twelve novel HGD gene variants identified in 99 alkaptonuria patients: focus on ‘black bone disease’ in Italy

Abstract: Alkaptonuria (AKU) is an autosomal recessive disorder caused by mutations in homogentisate-1,2-dioxygenase (HGD) gene leading to the deficiency of HGD enzyme activity. The DevelopAKUre project is underway to test nitisinone as a specific treatment to counteract this derangement of the phenylalanine-tyrosine catabolic pathway. We analysed DNA of 40 AKU patients enrolled for SONIA1, the first study in DevelopAKUre, and of 59 other AKU patients sent to our laboratory for molecular diagnostics. We identified 12 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 38 publications
2
74
1
1
Order By: Relevance
“…Although computational stability predictors have not been specifically designed to identify pathogenic mutations, they are very commonly used when assessing candidate disease mutations. For example, publications reporting novel variants will often include the output of stability predictors as evidence in support of pathogenicity [22][23][24][25] . This relies essentially upon the assumption that the molecular mechanism underlying many or most pathogenic mutations is directly related to the structural destabilisation of protein folding or interactions [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Although computational stability predictors have not been specifically designed to identify pathogenic mutations, they are very commonly used when assessing candidate disease mutations. For example, publications reporting novel variants will often include the output of stability predictors as evidence in support of pathogenicity [22][23][24][25] . This relies essentially upon the assumption that the molecular mechanism underlying many or most pathogenic mutations is directly related to the structural destabilisation of protein folding or interactions [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a high number of AKU cases were also found in Jordan (23) and India (18). Nemethova et al (24) reported 99 AKU patients with 12 novel mutations from Italy. In our study, 8 different AKU mutations with two new mutations were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Two comprehensive analysis on AKU causing mutations were carried out in an attempt to characterize the potential molecular mechanisms on which mutations could disruption enzyme activity 17,18 .…”
Section: Mendelian Genetic Diseasesmentioning
confidence: 99%